2002
DOI: 10.1046/j.1365-2273.2002.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk factors and gender in nasal polyposis

Abstract: The aetiology of nasal polyps remains obscure. Although clinically associated with asthma, notably in women, there is a marked male preponderance of polyposis. This study aimed to explore environmental pollutant triggers and gender differences in risk factors for nasal polyps. In total, 900 patients having surgery for polyposis and 120 new patients with nasal polyps completed a questionnaire with regard to occupational dust and chemical exposure. The male to female ratio was 2:1, and 52% were smokers, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
1
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 14 publications
6
26
1
8
Order By: Relevance
“…This too is troublesome because nasal disease with and without nasal polyps may be differently associated with smoking. COLLINS et al [19], HOUSER et al [20] and others have found smoking to be associated with nasal polyposis, a disease that is generally considered to be eosinophilic in nature, at least in Caucasians [59]. However, other studies have shown that sinonasal inflammation in COPD is skewed towards a neutrophilic response resembling CRS without nasal polyps [50][51][52]60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This too is troublesome because nasal disease with and without nasal polyps may be differently associated with smoking. COLLINS et al [19], HOUSER et al [20] and others have found smoking to be associated with nasal polyposis, a disease that is generally considered to be eosinophilic in nature, at least in Caucasians [59]. However, other studies have shown that sinonasal inflammation in COPD is skewed towards a neutrophilic response resembling CRS without nasal polyps [50][51][52]60].…”
Section: Discussionmentioning
confidence: 99%
“…COLLINS et al [19] and HOUSER et al [20] independently investigated the association between nasal polyps and smoking in two studies comprising 1020 and 373 patients, respectively. Both studies included patients undergoing surgery for nasal polyposis and they found the prevalence of smoking among nasal polyp patients to be 50-100% higher than in the background population.…”
Section: Smoking and Sinonasal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…De los casos en los que los pacientes sufren ambas enfermedades un 69% de ellos padecen el asma en primer lugar, un 21% desarrollan primero RSC-PN y el 10% restante los hace de forma prácticamente simultánea [23]. Además se ha determinado que los casos de pacientes femeninos que padecen ambas enfermedades duplican el de masculinos, al contrario de lo que ocurría en casos de RSC-PN generales, teniendo las pacientes femeninas que padecen PN una probabilidad 1,6 veces mayor de ser asmáticas y 2,7 veces mayor de ser alérgicas [24].…”
Section: Epidemiología De La Enfermedadunclassified
“…Соответственно уровень заболеваемости ПРС значительно выше, чем в приведенных официальных ис-точниках. Средний возраст пациентов для дебюта ПРС со-ставляет 42 года [6], мужчины подвержены этому заболева-нию чаще женщин в соотношении 2-3:1 [7].…”
unclassified